Growth-Stimulatory Effect of Quorum Sensing Signal Molecule N-Acyl-Homoserine Lactone-Producing Multi-Trait Aeromonas spp. on Wheat Genotypes Under Salt Stress - Nawaz, Muhammad Shoib; Arshad, Ayesha; Rajput, Lubna; Fatima, Kaneez; Ullah, Sami; Ahmad, Muhammad; Imran, Asma (Frontiers in Microbiology, 2020)
Salinity is one of the major threat to agricultural productivity worldwide. Soil and plant management practices alongwith inoculation with plant beneficial bacteria play a key role in plant’s tolerance towards salinity stress. Present study demonstrates the potential of AHLs-producing PGPR strains of Aeromonas sp. namely; SAL-17 (Accession no. HG763857), and SAL-21 (Accession no. HG763858) for growth promotion of two wheat genotypes inherently different for salt tolerance potential. Acyl homoserine (AHLs) are the bacterial signal molecules which regulate expression of various genes in bacteria and plants. Both Aeromonas spp. along with innate PGP and salt-tolerance traits showedAHL production which were identified on tandem mass spectrometry asC6-HSL, 3-OH-C5-HSL, 3-OH-C6-HSL, 3-oxo-C7-HSL C10-HSL, 3-oxo-C10-HSL, 3-OH-C10-HSL, 3-oxo-C12-HSL and C6-HSL, and 3-oxo-C10-HSL.The exogenous application of purified AHLs (mix) significantly improved various root parameters at 200 mM NaCl in both salt-sensitive (SSG) and salt-tolerant (STG) genotypes; where highest increase (≈80%) was observed where a mixture of both strain’s AHLs were used. Confocal microscopicobservations and root overlay assay revealed a strong root colonization potential of two strains under salt-stress. Inoculation response of both STG and SSG genotypes was evaluated with two AHLs-producing (SAL-17, SAL-21) and compared to non-AHL producing Aeromonas sp. SAL-12 (accession no. HG763856) in saline (EC=7.63ms/cm2) and non-saline soil.The data reveals that plants inoculated with bacterial consortium (SAL-21+SAL-17) showed maximum increase in leaf proline content, nitrate reductase activity, chlorophyll a/b, stomatal conductance,transpiration rate, root length, shoot length and grain weight over non-inoculated plants grown in saline soil. Both STG and SSG showed relative effectiveness towards inoculation (percent increase for STG: 165-16%; &SSG: 283-14%) and showed a positive correlation of grain yield with proline and nitrate reductase activity. Furthermore, PCA and CAT-PCA analysis clearly showed inoculation response in both genotypes revealing effectiveness of AHL-producing Aeromonas spp. than non-AHLs-producing strain. Present study documents that consortium of salt tolerant AHL-producing Aeromonas spp. is equally effective for sustaining growth of STG as well as SSG wheat genotypes in saline soil but biosafety should be fully ensured before field release.